ISOLATION AND CHARACTERIZATION OF HEXACHLOROCYCLOHEXANE DEGRADATION OF FILAMENTOUS FUNGAL STRAIN FNA33 FROM PESTICIDE DETOXIFICATION BY AEROBIC BIOREACTOR - Hà, Đặng Thị Cẩm (Vietnam Journal of Biotechnology, 2011)
Three filamentous fungal   sfrains  were isolated  of soil bioremediation freatment by aerobic bioreactor in order to detoxify DDT, HCH and other pesticides. These fimgal  strains FNA31, FNA32 and FNA33 cultivated in mineral   salt   medium   containing 300 ppm HCH and FNA33 showed the best grovrth.  Based   on   colony morphology,  sporephore  observed through  microscope  and  sequence  of  a partial   18S rRNA  gene, the   sfrain FNA33 could be classified Aspergillus sp. FNA33. The  18S rRNA gene fragment sequence oi Aspergillus sp. FNA33 was deposited in the GenBank database with assession number EU684231. After   14 days incubation in mineral salt medium  containing  0.5%   glucose,  Aspergillus  sp. FNA33  degraded  88% HCH with  initial concenfration   243 ppm. Furthermore, after   7 days in the same condition this sfrain   also produced   exfracellular enzyme   mangan   peroxidase   (434.5  U/l) and  laccase (4.3  U/l).  After  20 days of cultivation the   activity of manganese peroxidase detected still at high level (269 U/l)